ANALISIS PENDAPATAN DAN KEBERLANJUTAN USAHATANI PADI SAWAH ORGANDAN ANORGANIK DI KABUPATEN PRINGSEWU PROVINSI LAMPUNG - Luvita Willya Hendri; Raden Hanung Ismono; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The aim of this research is to compare the income and sustainability of organic and inorganic rice farming.  The study was conducted in Pringsewu District purposively by considering the area as one of the organic rice producers in Lampung Province. This study uses a survey method. Respondents in this research were 35 organic rice farmers and 35 inorganic rice farmers. The data analysis used is farm income analysis and sustainability index. Data analysis were carried out descriptively and differentially using the Independent SampleT-Test Parametric Test and the Mann-Whitney Nonparametric Sample Test.  The results showed that the income of organic and inorganic rice farming was profitable but there was no significant difference in income. Organic rice farming is a sustainable criterion, while inorganic rice farming includes criteria that are quite sustainable, and there was significant difference in sustainability between the two.Key word: farming, income, inorganic, organic, sustainability